Production of new/modified proteins in transgenic plants - Sonnewald, Uwe; et al. (1999)
In recent years, plant biotechnology has almost reached maturity. Transgenic plants engineered to be herbicide- or insect-resistant are outcompeting conventional crop plants and pest managing strategies leading to a major rethinking of the chemical industry. Due to worldwide efforts to study genome function, almost any gene of interest is, or will soon be available, Thus, identification of gene function will be the major challenge of the next few years. In combination with established gene-delivery systems and desired promoter and targetting sequences, gene discovery will open a fascinating and new field of crop plant design. Transgenic plants engineered to produce superior polypeptides have already been created and the first examples are entering clinical and industrial trials.